An Act to Regulate the Keeping and Beariing of Deadly Weapons, ch. 34, § 6, 1871 TEX. GEN. LAWS 1ST SESS. 25, 25-27 (1898 Gammel Book Company) - (:unkn) unknown (General Publisher, 1871)
It shall be the duty of any sheriffs, constables, marshals, and their deputies, and all policemen, to enforce §§ 1-3 of this law regulating carry, self-defense claims, and sensitive places.
--
Keywords: PEACE OFFICERS